Effect of ınquiry-based science activities on prospective elementary teachers’ use of science process skills and ınquiry strategies - Özdemir, Oğuz; Işık, Hakan (Journal of Turkish Science Education, 2015)
In this study, the effect of science activities designed by inquiry-based approach on prospective elementary teachers’ utilization of science process skills and inquiry strategies is investigated. The study was conducted by a group of prospective elementary teacher (N=119) established by mean of purposed sampling. Data was gathered pre and post instructional practices of the instruments “science process skills and strategies (S&S)- scale” and “science process skills (SS)-test”. The data were analyzed by procedures of dependent group t-test and Pearson correlation test which pointed an effect of inquiry - based activities on the prospective teachers` use of science process skills and inquiry strategies. The study concludes with recommendations for further investigations to signify and overcome the barriers challenging the prospective teachers’ adaptations and practices of science process skills and inquiry strategies.
Keywords: Inquiry-Based Teaching; Inquiry Strategies; Prospective Elementary Teachers; Science Process Skills; Science Teacher Education